The influence of genetic variability of DNA repair mechanisms on the risk of malignant mesothelioma - Levpušček, Kristina (Radiology and oncology (Ljubljana), 2019)
Malignant mesothelioma (MM) is a rare aggressive tumour of mesothelium caused by asbestos exposure. It has been suggested that the genetic variability of proteins involved in DNA repair mechanisms affects the risk of MM. This study investigated the influence of functional polymorphisms in ERCC1 and XRCC1 genes, the interactions between these polymorphisms as well as the interactions between these polymorphisms and asbestos exposure on MM risk. Patients and methods. In total, 237 cases with MM and 193 controls with no asbestos-related disease were genotyped for ERCC1 and XRCC1 polymorphisms. Results. ERCC1 rs3212986 polymorphism was significantly associated with a decreased risk of MM (odds ratio OR = 0.61; 95% confidence interval (CI = 0.41%0.91; p = 0.014). No associations were observed between other genetic polymorphisms and MM risk. Interactions between polymorphisms did not significantly influence MM risk. Interaction between ERCC1 rs11615 and asbestos exposure significantly influenced MM risk (OR = 3.61; 95% CI = 1.12%11.66; p = 0.032). Carriers of polymorphic ERCC1 rs11615 allele who were exposed to low level of asbestos had a decreased risk of MM (OR = 0.40; 95% CI = 0.19%0.84; p = 0.016). Interactions between other polymorphisms and asbestos exposure did not significantly influence MM risk.
Keywords: DNA repair mechanisms; DNK; genetic polymorphism; genetski polimorfizem; malignant mesothelioma; maligni mezoteliom; mehanizem popravljanja napak